Effect of Impeller-To-Tank Geometry on Particles Distribution and Just-Suspension Speeds for a Range of Solids Loadings - Wong, S.D.; Ibrahim, S.; Zamzam, Z.; Kato, Y.; Sato, M. (Society of Chemical Engineers, Japan, 2015)
Particle distribution and just-suspension speeds have been studied for SATAKE SUPERMIX® HR100 and HS604 impellers in comparison to a 45° pitched-blade turbine (4PBT) and propeller (3P) in a flat-base fully baffled cylindrical tank. The slurries were made up of 18.0 µm, 75.3 µm and 195.5 µm diameter PMMA particles in water, with solids loading ranging from 5 to 40% by weight. Points of last suspension were either from the center, side, or annular region, and are directly related to the flow on the tank base, which could result from primary discharge or induced flow. Increasing impeller clearance from the base reduces the extent of flow for the 4PBT and 3P, such that at high clearances the main flow completely separates into two recirculating loops, with weaker secondary loops in the lower half of the tank. This led to the accumulation of particles at the tank center. By comparison, the HR100 generates a strong axial flow that was maintained at all clearances, thereby making it more advantageous in clearing particles at the tank center. Njs increased with increasing C/D, particularly at high clearances for the 4PBT and 3P, while the HR100 is relatively less affected by clearance. At C/D=0.75 and 1.0, Njs for both the 4PBT and 3P are strongly affected by solids loading of 20 wt% and upwards. The HS604 has promising suspension performance in terms of stability with respect to changes in solids loading, and this is related to its discharge pattern that results from a very low clearance.